Melalui Model Projects Based Learning Metode Diskusi Kelompok untuk Mengoptimalisasi Aktifitas Dan Hasil Belajar Peserta Didik Pada Mapel PPKn, Materi Harmoni dalam Keberagaman Sosial, Budaya, Gender dalam Bingkai Bhineka Tunggal Ika Kelas IX.4 MTsN 1 P - Afni Wira Yulia (Departement of Mathematics Education, 2022)
The purpose of this Classroom Action Research is to improve the learning outcomes of Citizenship Education on the subject of Harmony in Social Diversity, Culture, Gender in the Bhineka Tunggal Ika Frame of students in class IX 4 Academic Year 2021/2022 by using a Scientific Approach Project Based Learning learning model. This research was conducted for 20 weeks from January to May 2022 (9 meetings) with two cycle methods, namely cycle I knowledge and cycle I skills as well as cycle II. The first cycle of knowledge consists of three meetings, the third meeting is the daily test of the first cycle of knowledge and the daily test of skills and the second cycle for knowledge and skills consists of planning, action, observation, and reflection. The subjects of this study were students of class IX 4 even semester of MTsN 1 Payakumbuh Academic Year 2021/2022. The data collection technique is by holding daily exams for each cycle as a result of student learning. The results obtained from this study are participatory discussions can increase students' activities and learning outcomes. This is evident from the results obtained in Cycle I 55.2% for student activity in cycle II rose to 77.5% for learning activities or an increase of 22.3%. In Cycle I the knowledge of the percentage of learning outcomes of students from 61.2% to 89% in Cycle II or an increase of 27.8% for Knowledge learning outcomes and in the first cycle of Skills the percentage of students' learning outcomes from 75% to 86% in the Cycle Cycle II or an increase of 11% for Skills learning outcomes. The conclusion of this study is that learning using the Scientific method Project Based Learning model can improve student learning outcomes so that fellow teachers can make reference to vary the learning methods implemented in schools.